Birth and death notification via mobile devices - Vasudevan, Lavanya (Cochrane Database Syst Rev, 2018)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: PRIMARY OBJECTIVES: To assess the effects of birth notification via a mobile device, compared to standard practice. To assess the effects of death notification via a mobile device, compared to standard practice. SECONDARY OBJECTIVES: To describe the range of strategies used to implement birth and death notification via mobile devices. To identify factors influencing the implementation of birth and death notification via mobile devices.